Frequency of hospitalizations due to hemolytic uremic syndrome in children from 0 to 14 years of age in Peru, period 2015 to 2022 - Atamari-Anahui, Noé (2023)
Introduction. There are limited epidemiological reports of hemolytic uremic syndrome (HUS) in Latin America. Objective. To describe the frequency and characteristics of hospitalizations due to HUS in children aged 0 to 14 years. Methods. Descriptive study of secondary analysis was performed with data on hospitalizations due to HUS from healthcare institutions from Peru, 2015-2022. Results. Two hundred twenty-eight hospitalizations were registered, 52.2% were male, 88.6% were under five years old, and 11% were under one year old. The departments with more hospitalizations were Lima (133 cases) and Arequipa (46 cases). The institutions of the Ministry of Health (MINSA) and Social Security (EsSalud) reported 42.5% and 27.6% of hospitalizations. From 2015 to 2022, the incidence ranged from 0.42 to 1.13 cases/100,000 children under five years of age. Conclusions. Hospitalizations due to HUS were more frequent in children under five years of age and MINSA institutions.